Finding that Fine Balance Between Tradition and Innovation in the Language Classroom - Saroli, Anna (CIEX JOURNAL, 2016)
The rate of innovation in the language classroom has increased exponentially in the past decades, and teachers may feel pressured to use the latest technologies or approaches without any real evidence that these new methods are more effective. This paper considers innovation from the perspective of finding a balance in teaching between methods that have been developed over the years and newer approaches, and concludes that we will be better teachers if we are allowed to welcome innovation on our own terms.